10-year-old with concha bullosa pyogenic mucocele. (15th May 2018) - Fuglsang, Milos; Sørensen, Leif Hovgaard; Petersen, Kristian Bruun; Bille, Jesper
Abstract : A 10-year-old girl presented with episodes of migraine. A nasal mass was found randomly during work-up. Interpreted as an osteoma, the mass was removed during endoscopic surgery. However, the histopathological examination turned out to be a pyomucocele in the right middle turbinate, which is an extremely rare yet benign condition in children.